An Open-Label Safety and Pharmacokinetics Study of Duloxetine in Pediatric Patients with Major Depression - Prakash, Apurva; Lobo, Evelyn; Kratochvil, Christopher J.; Tamura, Roy N.; Pangallo, Beth A.; Bullok, Kristin E.; Quinlan, Tonya; Emslie, Graham J.; March, John S. (Journal of child and adolescent psychopharmacology, 2012)
This preliminary, 32-week study assessed the safety, tolerability, and pharmacokinetics of duloxetine in pediatric patients (aged 7-17 years) with major depressive disorder. Patients received flexible duloxetine doses of 20-120 mg once daily, with dose changes made based on clinical improvement and tolerability. Pharmacokinetic samples were collected across all duloxetine doses, and data were analyzed using population modeling. Primary outcome measures included treatment-emergent adverse events (TEAEs), vital signs, and Columbia-Suicide Severity Rating Scale (C-SSRS). Of the 72 enrolled patients, 48 (66.7%) completed acute treatment (18 weeks) and 42 (58.3%) completed extended treatment. Most patients (55/72; 76%) required doses ≥ 60 mg once daily to optimize efficacy based on investigator judgment and Clinical Global Impressions-Severity score. Body weight and age did not significantly affect duloxetine pharmacokinetic parameters. Typical duloxetine clearance in pediatric patients was ≈ 42%-60% higher than that in adults. Four patients (5.6%) discontinued due to TEAEs. Many (36/72, 50%) patients experienced potentially clinically significant (PCS) elevations in blood pressure, with most cases (21/36, 58%) being transient. As assessed via C-SSRS, one nonfatal suicidal attempt occurred, two patients (2.8%) experienced worsening of suicidal ideation, and among the 19 patients reporting suicidal ideation at baseline, 17 (90%) reported improvement in suicidal ideation. Results suggested that pediatric patients generally tolerated duloxetine doses of 30 to 120 mg once daily, although transient PCS elevations in blood pressure were observed in many patients. Pharmacokinetic results suggested that adjustment of total daily dose based on body weight or age is not warranted for pediatric patients and different total daily doses may not be warranted for pediatric patients relative to adults.